27.8k views
17 votes
2t + 4(4 + 10t)
Simplify the expression

User Layman
by
5.6k points

2 Answers

0 votes

Simplify the expression

2t + 4(4 + 10t)

Simplifying

y = 2t4 + -10t2 + 13

Reorder the terms:

y = 13 + -10t2 + 2t4

Solving

Solving for variy = 13 + -10t2 + 2t4

able 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying

y = 13 + -10t2 + 2t4

Hence the information I've given you, we can now state that the answer is

42 t + 16

User RealSteel
by
5.1k points
3 votes

Answer:

=42t+16

Explanation:

=2t+(4)(4)+(4)(10t)

=2t+16+40t

=2t+16+40t

=(2t+40t)+(16)

=42t+16

User Jessica Alan
by
5.7k points